Cultural care observation from Leininger’s perspective. (Colombia Medica, 2007)
Introduction: Understanding care from Leininger’s perspective implies learning about people’s living ways, their environments, their feelings, their worries, their beliefs, their practices as well as their values in different events, such as motherhood, fatherhood, birth, adolescence, adultness, elderliness, diseases and death, with the main objective of offering a care agreeable and compatible to their culture. Research and practice in transcultural nursing: This learning related to the care that persons have by themselves, necessarily indicates or suggests an interaction with them. However, an interaction requires preparation, sensitiveness and a critical thought in order to discover and to grasp all of the different meanings that people give to their lives and their own care. Reflection: This investigation has been configured as an entry door to get those points of view and as a bridge to approximate the professional nursing towards quotidian people’s lives in order to obtain knowledge from them.